PENGELOLAAN SURAT KELUAR BERBASIS WEB DI DISKOMINFO PROVINSI BANTEN - Asep Sapaatullah; Rahadian Arief; Waro Khoirunnisa; Rustam Effendi; Hamid Al Jufri; Yasin Efendi (LPPM Universitas Bina Bangsa, 2022)
The Office of Communication, Informatics, Encryption and Statistics of Banten Province often experiences problems in managing letters, especially when searching for the desired letter takes a long time and when making reports whose results are not accurate, this is because there are still many errors in the data recording process and still using the system. which is manual where the recording is still using a ledger and making letters is still manual, namely making in word. To make it easier to collect outgoing mail, a system that has good data recording and storage is needed. Based on the existing problems, the researcher proposes a new system in managing outgoing mail, and has a storage area in the form of an information system. The outgoing mail system at Diskominfo Banten Province was developed using the PHP programming language with MYSQL database, the research method used was the flowmap method, DFD (Data Flow Diagram) with waterfall development, while the data collection techniques used in this study were interviews, observation and literature review. With this web-based outgoing mail management information system, it can make it easier to make letters, record letters, archive letters and report letters, besides that this system is expected to better support employee performance/activities in managing mail data.